Świat przyrody w Rejowym opisywaniu faz życia ludzkiego - Kozaryn, Dorota (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2010)
The aim of the article is the presentation of the literary means selected by Mikołaj Rej in his writings, the means using the natural world to describe the stages of human life. On the basis of the conducted analysis it can be concluded that the author from Nagłowice, in order to describe the young age, maturity and the old age, uses references to the seasons, the times of day, animals, plants, water and atmospheric phenomena.